Effect of foot solar plexus reflexology on severity of nausea and vomiting at first half of pregnancy: A Randomized Clinical Trial - Fatemeh Asadollahi; Raheleh Babazadeh; Hamid Abdi; Habibollah Esmaeily (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2019)
Introduction: Nausea and vomiting are among the most common gastrointestinal complaints of women at beginning of pregnancy that can cause many social and individual problems. Since no study was found on the effect offoot solar plexus reflexology on nausea and vomiting of pregnancy in Iran, this study was performed with aim to evaluate the effect of solar plexus reflexology on severity of nausea and vomiting at first half of pregnancy. Methods: This randomized clinical trial was conducted on 73 pregnant women at 8-20 weeks of pregnancy who referred to one of the health care centers of Najafi, Amiralmomenin and Vahdat, Mashhad in 2018. The subjects were randomly divided into two groups of reflexology (n=36) and control (n=37). This study was conducted for 10 days in three steps; the scores of nausea and vomiting were measured by Rhodes Index. No intervention was done on days 1 to 3. On days 4 to 7, intervention group received one session of foot reflexology daily for 20 minutes with emphasis on solar plexus point, and the control group received only routine care. On days 8 to10, no intervention was performed. Data were analyzed by SPSS software (version 25) and variance analysis, Chi-square and independent t-test. P<0.05 was considered statistically significant. Results: The changes in mean score of nausea, vomiting and retching after the intervention had significant decrease in the intervention group compared to control group as 0.36 unit ( p = 0.04 ), 0.77 unit ( p< 0.001) and 0.46 unit ( p= 0.004), respectively. Conclusion: Foot solar plexus reflexology has positive effect on gestational nausea, vomiting and retching. Since gestational nausea and vomiting is common and reflexology is safe, the use of this technique is recommended in pregnancy.